2013
DOI: 10.4028/www.scientific.net/msf.755.47
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Ball-Milling of FeAl<sub>2</sub> and Fe<sub>2</sub>Al<sub>5</sub> Intermetallic Systems

Abstract: In this study, FeAl2 and Fe2Al5 intermetallic alloys were prepared by conventional casting technique. In order to study their structural stability the alloys were subjected to high-energy ball milling process for 1, 2.5, 5 and 10 h. The structural and chemical characterizations were conducted by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and differential scanning calorimetry. After 10 h of milling, the experimental results indicated a phase transformation from FeAl2-tricl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A comparison of the phases formed in Al-Fe alloys as analysed from the X-ray diffraction (XRD) traces is given in Table 2. In addition to MA experiments, Romero et al [22] reported the effect of mechanical milling (MM) on the structural evolution of as-cast Al 2 Fe and Al 5 Fe 2 intermetallic systems at different short milling times. Apart from this study, no other reports on systematic investigation on the structural evolution of as-cast Al-rich iron aluminide intermetallics are available.…”
Section: Al-fe Intermetallics By Mechanical Alloying/mechanical Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the phases formed in Al-Fe alloys as analysed from the X-ray diffraction (XRD) traces is given in Table 2. In addition to MA experiments, Romero et al [22] reported the effect of mechanical milling (MM) on the structural evolution of as-cast Al 2 Fe and Al 5 Fe 2 intermetallic systems at different short milling times. Apart from this study, no other reports on systematic investigation on the structural evolution of as-cast Al-rich iron aluminide intermetallics are available.…”
Section: Al-fe Intermetallics By Mechanical Alloying/mechanical Millingmentioning
confidence: 99%
“…This process will result in a lower bound for the grain size of pure metals and alloys and reveals that a small grain size itself provides a limit for further grain refinement on milling. On the whole, when the material exhibits a nanocrystalline Al-25 at.%Fe Al 5 Fe 2 Cardellini et al [20] Al-20 at.%Fe Amorphous Zhou et al [17] Al-20 at.%Fe Al 5 Fe 2 Cardellini et al [20] Al-34 at.%Fe α-Al Enzo et al [19] Al-17-33 at.%Fe Amorphous Huang et al [18] Al-25 at.%Fe α-Al Enzo et al [19] Al-33.28 at.%Fe Al 5 Fe 2 + Al 2 Fe Romero et al [22] Intermetallic Compounds -Formation and Applications structure, hence microstructural refinement cannot be observed and further deformation can only be accomplished by grain boundary sliding (GBS). It has been suggested that the minimum grain size that can be achieved by milling is determined by the balance between defect/ dislocation structure introduced by the plastic deformation of milling and its recovery by thermal processes.…”
Section: Nanostructured Materialsmentioning
confidence: 99%
“…Hirata et al [18] studied the crystal structure of Al 2 Fe and Al 5 Fe 2 phases and found that the crystal structure of the two phases has a similar decagonal-like atomic arrangement. Romero-Romero et al [19] studied the structural stability of Al 2 Fe and Al 5 Fe 2 phases by the high-energy ball-milling method. They found that the Al 2 Fe phase underwent a phase transition and transformed into the Al 5 Fe 2 phase after 10 h of high-energy ball milling.…”
Section: Introductionmentioning
confidence: 99%